2016
DOI: 10.1148/radiol.2015141624
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Imaging of Ethiodized Oil–loaded Radiopaque Microspheres during Transarterial Embolization of Rabbits with VX2 Liver Tumors

Abstract: equally to this work.q RSNA, 2015 Purpose:To assess the visibility of radiopaque microspheres during transarterial embolization (TAE) in the VX2 rabbit liver tumor model by using multimodality imaging, including singlesnapshot radiography, cone-beam computed tomography (CT), multidetector CT, and micro-CT. Materials and Methods:The study was approved by the institutional animal care and use committee. Fifteen VX2-tumor-bearing rabbits were assigned to three groups depending on the type of embolic agent inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Additionally, our work showed that SPECT/photoacoustic imaging mediated by 131 I-HCuSNPs-MS-PTX could help to confirm the delivery of the microspheres to the targeted tumors and to guide therapy planning for near-infrared laser irradiation. Previous studies have focused on embolic microsphere detection with CT and magnetic resonance (MR) imaging 67 - 69 ; however, the high sensitivity of SPECT/CT and high specificity of photoacoustic imaging in our study obviated the need for additional imaging.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, our work showed that SPECT/photoacoustic imaging mediated by 131 I-HCuSNPs-MS-PTX could help to confirm the delivery of the microspheres to the targeted tumors and to guide therapy planning for near-infrared laser irradiation. Previous studies have focused on embolic microsphere detection with CT and magnetic resonance (MR) imaging 67 - 69 ; however, the high sensitivity of SPECT/CT and high specificity of photoacoustic imaging in our study obviated the need for additional imaging.…”
Section: Discussionmentioning
confidence: 87%
“…In the clinical setting, after embolization with standard microspheres, such imaging features can be achieved only with a low degree of reproducibility since the iodinated contrast agent is rapidly and unpredictably washed out [ 13 , 24 , 25 ]. Moreover, the transient intratumoral contrast agent saturation may not represent the exact location of the microspheres but mainly stasis of the iodinated contrast agent column [ 12 , 13 , 24 , 29 ]. Using inherently radiopaque microspheres, the true intra- and peritumoral microsphere distribution could be assessed objectively, and treatment endpoints could be optimized and standardized (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Using inherently radiopaque microspheres, the true intra- and peritumoral microsphere distribution could be assessed objectively, and treatment endpoints could be optimized and standardized (e.g. by using microsphere quantification techniques for the embolized target volume) [ 12 , 13 , 30 ]. Another important issue is the sensitivity of the imaging method which is being used for visualizing radiopaque embolic agents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations